Using small world toys for research: a method for gaining insight into children's lived experiences of school. Issue 3 (27th May 2021) - Gripton, Catherine; Vincent, Kerry
ABSTRACT: The importance of children's perspectives is now well-established and there has been much attention afforded to appropriate methods for listening to children within the research. Whilst language-based research methods, such as interview, remain commonplace, children's representations are increasingly included as data in educational research. Photographs, drawings and tours have been used alongside the traditional tools of observation and interview to illuminate children's understanding of their school experiences but more are needed. This paper reports on an addition to this repertoire of tools, small world toys, and finds that valuable insight can be gained through using them as a data collection method. Drawing on research into children's lived experiences of school, it outlines the affordances and key principles of this method. It argues that capturing the process as well as the outcome is key in using small world toy representations and that using them in collaboration with other methods is needed in order to gain rich, reliable data. It concludes that whilst ethical praxis is key in using any method to research children's perspectives, crafting new and bespoke methods to more authentically hear and take account of children's perspectives should be an important and ongoing endeavour of researchers in this field.